Boulevard of dreams - Gonzalez, Mandy; Thurman, Brittany (Gonzalez, Mandy. Fearless (Series), 2023)
Twelve-year-old Relly Morton hopes that his hit Broadway show will help his Grandpa Slyde change his mind about his grandson's love for theater, but during the performance, a wrong step sends the whole cast back to the 1950s. It is in that time that Relly meets his young grandfather, who had dreams of his won in show business. Something happened to make Grandpa Slyde give up his dream. Relly must find out what it was, and get back to the present in time for their show.